2021
DOI: 10.3389/fphar.2021.730557
|View full text |Cite
|
Sign up to set email alerts
|

Eucommia ulmoides Polysaccharides Attenuate Rabbit Osteoarthritis by Regulating the Function of Macrophages

Abstract: Background and purpose:Eucommia ulmoides polysaccharides (EUP) can regulate the immunity of macrophages, but the functional status of macrophages is related to osteoarthritis and synovial inflammation. The purpose of this study is to explore whether EUP has the effect of inhibiting osteoarthritis and its possible mechanism.Methods: MTT test was used to evaluate the appropriate concentration of EUP and real-time quantitative polymerase chain reaction (RT-qPCR) was conducted to detect the effect of EUP on gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Pharmacological studies have shown that the extracts of EU inhibit the progression of OA by inhibiting the PI3K/Akt pathway (Xie et al, 2015). EU extract can promote articular cartilage repair and subchondral bone reconstruction by regulating the function of macrophages (Sun, Huang, et al, 2021). Therefore, it is expected that EULs are capable of having potent anti‐osteoarthritis effects.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies have shown that the extracts of EU inhibit the progression of OA by inhibiting the PI3K/Akt pathway (Xie et al, 2015). EU extract can promote articular cartilage repair and subchondral bone reconstruction by regulating the function of macrophages (Sun, Huang, et al, 2021). Therefore, it is expected that EULs are capable of having potent anti‐osteoarthritis effects.…”
Section: Introductionmentioning
confidence: 99%
“…Six of the ten active ingredients with high degree values were from Eucommia tulipifera (E. tulipifera) and the associated components of E. tulipifera, such as quercetin and kaempferol, were connected to drug-disease common targets with high density, suggesting that E. tulipifera may play a good role in the treatment of PMO. The lignans and phenylpropanoids in Eucommia are immuneenhancing, and the sterol in bone marrow is used as a raw material for the production of vitamin D3, so it is assumed that QEP may prevent PMO exacerbation to some extent [28][29][30][31][32][33][34] . The topological analysis of the main compounds and the major intersecting targets revealed the highest binding of the target CYP3A4 and hirsutine.…”
Section: Resultsmentioning
confidence: 99%
“…is an important warming and toxifying kidney-yang herb for the treatment of waist and knee pain, joint disadvantage and muscle and bone weakness. [29][30][31] Glycyrrhiza uralensis Fisch. is a qi-invigorating herb, which has been proven to enhance the functions of immunity, anti-inflammatory, anti-gastric ulcer, anti-arrhythmia and regulate blood glucose.…”
Section: Discussionmentioning
confidence: 99%